Super-Resolution Microscopy Reveals a Nanoscale Organization of Acetylcholine Receptors for Trans-Synaptic Alignment at Neuromuscular Synapses - York, Amanda L. (eNeuro, 2017)
The neuromuscular junction (NMJ) is a chemical synapse formed between motoneurons and skeletal muscle fibers. The vertebrate NMJ uses acetylcholine (ACh) as the neurotransmitter and features numerous invaginations of the postsynaptic muscle membrane termed junctional folds. ACh receptors (AChRs) are believed to be concentrated on the crest of junctional folds but their spatial organization remains to be fully understood. In this study, we utilized super-resolution microscopy to examine the nanoscale organization of AChRs at NMJ. Using Structured Illumination Microscopy, we found that AChRs appear as stripes within the pretzel-shaped mouse NMJs, which however, do not correlate with the size of the crests of junctional folds. By comparing the localization of AChRs with several pre- and postsynaptic markers of distinct compartments of NMJs, we found that AChRs are not distributed evenly across the crest of junctional folds as previously thought. Instead, AChR stripes are more closely aligned with the openings of junctional folds as well as with the presynaptic active zone. Using Stochastic Optical Reconstruction Microscopy (STORM) for increased resolution, we found that each AChR stripe contains an AChR-poor slit at the center that is equivalent to the size of the opening of junctional folds. Together, these findings indicate that AChRs are largely localized to the edges of crests surrounding the opening of folds to align with the presynaptic active zones. Such a nanoscale organization of AChRs potentially enables trans-synaptic alignment for effective synaptic transmission of NMJs.